EFEKTIVITAS PELATIHAN PEMANFAATAN JAMU SEBAGAI SUPLEMEN BAGI SAPI BAGI PETERNAK DI KAMPUNG MIMI BARU DISTRIK JAGEBOB - Nurcholis Nurcholis; Syetiel Maya Salamony; Dirwan Muchlis (Musamus University, 2019)
Cattle productivity is generally influenced by several factors including feed, animal feed which have an important role in increasing livestock production, beside the feed factors, disease caused by parasites such as worms is a problem for farmers to increase cattle weight gain. Cows in Mimi Baru village have the potential to be developed because the feed land is quite high, but the situation that occurs is the cows in Mimi Baru village have body size (BCS) 3, it means that there needs to be nutrient repair therefore one way to improve it is to add supplements herbs and applying technology in the form of adding probiotics in herbs to increase appetite, health and productivity of cattle. The objective of this training is to increase knowledge for cattle farmers to increase the productivity of their livestock by utilizing herbal plants as supplements. The result of direct training to farmers in Mimi Baru village in making herbal herbs as supplements were responded very positively by the participants of the activity because it was recognized to be very helpful to reduce the risk of cow worms and eat the mine. The number of cattle identified was exposed to worms by 40 cows and nearly 75% of all cows in Mimi Baru village ate ropes. Keywords: Training, herbal medicine, Mimi Baru village